2016
DOI: 10.7439/ijbar.v7i6.3356
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Hepatitis B and Hepatitis C in haemodialysis population in a tertiary care centre in north eastern India

Abstract: Background: Prevalence of Hepatitis B Virus (HBV) and Hepatitis C Virus (HCV) in the haemodialysis (HD) population varies between 3.4-45% and 4.3-45.2% respectively which are substantially higher than the prevalence rates in the general population. We conducted a study to estimate the prevalence of HBV and HCV in HD population in a tertiary care centre in north east India. Methods: Prospective single centre observational study conducted in patients attending a HD unit between November 2012 and June 2015. All p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 7 publications
(10 reference statements)
0
3
0
Order By: Relevance
“…In this study, sero-occurrence of HCV co-infection in HBV patients was found to be low (1.67%) compared to global data, but higher than reported in other parts of India7,12,19. A large multicenter study from the United States assessed the prevalence of HBV/HCV co-infection and found anti-HCV was present in 7% of chronic HBV carriers10.…”
Section: Discussionmentioning
confidence: 41%
“…In this study, sero-occurrence of HCV co-infection in HBV patients was found to be low (1.67%) compared to global data, but higher than reported in other parts of India7,12,19. A large multicenter study from the United States assessed the prevalence of HBV/HCV co-infection and found anti-HCV was present in 7% of chronic HBV carriers10.…”
Section: Discussionmentioning
confidence: 41%
“…In our study, 23 patients (38.3%) had frequency “once a week” and 22 patients (36.6%) were with a frequency of dialysis “thrice a week.” In a study by Jamil, the majority of the population (69.82%) had once weekly dialysis, whereas 14.40% and 0.79% underwent dialysis on a twice-weekly or thrice-weekly basis. [ 13 ] The frequency of dialysis depends on the patient’s requirement. Due to multiple practices of dialysis, these patients are more prone to HCV and HBsAg infection.…”
Section: Discussionmentioning
confidence: 99%
“…The data presented in Table 4 indicate that during the period from 1993 to 2010, the seroprevalence of HCV in HD patients ranged from 12.1% to 46%, [19][20][21][22][23][24][25] whereas studies conducted after 2010 reveal a general decline in prevalence to 12.4%. [26][27][28][29][30] One exception in this regard, however, is a study conducted in Jammu in 2016, which reported a considerably higher prevalence of 31.4%. 31 We speculate that this wide divergence in prevalence could be attributed to a number of contributory factors, including different geographical locations, a different study duration, or differences in the sensitivity and specificity of the methods used for detecting HCV infection.…”
Section: Seroprevalence Of Hcvmentioning
confidence: 99%